Epigenomics in Environmental Health - Marsit, Carmen J.; Christensen, Brock C. (Frontiers in Genetics, 2011)
This review considers the emerging relationships between environmental factors and epigenetic alterations and the application of genome-wide assessments to better define these relationships. First we will briefly cover epigenetic programming in development, one-carbon metabolism and exposures that may disrupt normal developmental programming of epigenetic states. In addition, because a large portion of epigenetic research has focused on cancer, we discuss exposures associated with carcinogenesis including asbestos, alcohol, radiation, arsenic, and air pollution. Research on other exposures that may affect epigenetic states such as endocrine disruptors is also described, and we also review the evidence for epigenetic alterations associated with aging that may reflect cumulative effects of exposures. From this evidence, we posit potential mechanisms by which exposures modify epigenetic states, noting that understanding the true effect of environmental exposures on the human epigenome will require additional research with appropriate epidemiologic studies and application of novel technologies. With a more comprehensive understanding of the affects of exposures on the epigenome, including consideration of genetic background, the prediction of the toxic potential of new compounds may be more readily achieved, and may lead to the development of more personalized disease prevention and treatment strategies.